PENGAMBILAN ZAT WARNA ALAMI DARI KAYU NANGKA - Dany Eka Parasetia; R Ritaningsih; P Purwanto (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Textile dyes are divided into two, namely natural dyes and synthetic dyes. Natural dyes derived fromanimals and plants while the synthesis of dyes can be produced from these chemicals. Jackfruit plants is one type ofplant that can be utilized as a source of natural dyes for textiles by the wood extract. Manufacture of dyes from thejackfruit wood performed by the method of continue extractionoe with a soxhlet.Extraction results in the ratio 1: 15 that is the longer the extraction time the higher the yield obtained. Theoptimum time for extraction is 5 hours with a yield of 2.62% obtained for wood powder and shavings in 1:31% forwater content in the material 10%. While on the water content of 50% results in a material obtained by extraction of2.08% for wood powder and 1.08% for the shavings. In the ratio 1: 10 gained 1.68% yield for wood powder andshavings to 0.94% for water content in the material 10%. While on the water content of 50% results in a material is1.43% to 0.89% sawdust and shavings for.A very influential variable is the size of material and moisture content in the material. In the extraction ofdyes, solvents with a ratio of 1:15, the water content of 10% and the size of 100 mesh material produced the greatestyield of 2.62% obtained by linear regression is Y = 1.328 + 0256 x with a percent error of 0.16%.In the test fabric made with two methods ie with loundrymeter method for washing and methods crockmeterfor the desecration. Results of analysis of the fabric that has been colored later in the match with a grayscale andstainning scale.